RECONSTRUCTION OF WAYANG ORANG DARMA KERTI AT BATU PANDANG: A STRUGGLE FOR IDENTITY IN MATARAM, LOMBOK - Seramasara, I Gusti Ngurah; Ardhana, I Ketut; Suarka, I Nyoman; Ruastiti, I Made (E-Journal of Cultural Studies, 2016)
Wayang Orang (the stage show usually with the wayang theme) is a performing art of which the characters are played by people. As a specific Sasak performing art, the wayang orang which is performed in Mataram Lombok, used to use what is referred to as Serat Menak as the story source. However, such a performing art was marginalized and was almost getting extinct. Therefore, the Sasak artists and cultural observers, whom were facilitated by UPTD Taman Budaya Lombok, did their best to save such a performing art by reconstructing it. The performing art which was constructed by IPTD Taman Budaya Lombok was the Wayang Orang Darma Kerti , Dusun Batu Pandang . Such a reconstruction was made in the middle of the struggle for an identity of those living in Mataram, Lombok, who belong to different ethnic groups and religions. This present study was intended to understand the matter pertaining to the reconstruction of Wayang Orang Darma Kerti as part of the struggle for the identity of the people living in Mataram, Lombok. The qualitative method and the theories of deconstruction, multiculturalism, and hegemony were used to analyze the problems of the study. The result of the study showed that 1) there was a desire to preserve Wayang Orang as a local identity, meaning that the desire to reconstruct it was inspired by the Islamic religious value and the Wetu Telu Islamic value; 2) it was reconstructed through several stages; they are observation, inventory, and classification; finally, it was decided to reconstruct Wayang Orang performed at Dusun Batu Pandang, East Lombok in which the puppeteers and dancers from Mataram, West Lombok, were involved; the puppeteers were gathered, the themes were composed, the performance was practiced, and the Wayang Orang was performed; 3)  the implication of the reconstruction of the Wayang Orang was that the Sasak ethnic group had an art identity, and religion and culture adapted to each other as the implementation of what is referred to as adatluwirgama , and the local people’s prosperity became better.
Keywords: Reconstruction, Wayang Orang